A Consensus Parameter for the Evaluation and Management of Angioedema in the Emergency Department. (April 2014) - Moellman, Joseph J.; Bernstein, Jonathan A.; Lindsell, Christopher; Banerji, Aleena; Busse, Paula J.; Camargo, Carlos A.; Collins, Sean P.; Craig, Timothy J.; Lumry, William R.; Nowak, Richard; Pines, Jesse M.; Raja, Ali S.; et al.
Abstract Despite its relatively common occurrence and life‐threatening potential, the management of angioedema in the emergency department (ED) is lacking in terms of a structured approach. It is paramount to distinguish the different etiologies of angioedema from one another and more specifically differentiate histaminergic‐mediated angioedema from bradykinin‐mediated angioedema, especially in lieu of the more novel treatments that have recently become available for bradykinin‐mediated angioedema. With this background in mind, this consensus parameter for the evaluation and management of angioedema attempts to provide a working framework for emergency physicians (EPs) in approaching the patient with angioedema in terms of diagnosis and management in the ED. This consensus parameter was developed from a collaborative effort among a group of EPs and leading allergists with expertise in angioedema. After rigorous debate, review of the literature, and expert opinion, the following consensus guideline document was created. The document has been endorsed by the American College of Allergy, Asthma & Immunology (ACAAI) and the Society for Academic Emergency Medicine (SAEM).